2010
DOI: 10.1001/archophthalmol.2010.233
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection in Ocular Adnexal Lymphomas

Abstract: To assess the influence of hepatitis C virus (HCV) infection on disease appearance and outcome of ocular adnexal non-Hodgkin lymphoma (ONHL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 25 publications
(52 reference statements)
1
9
0
1
Order By: Relevance
“…Patients with HCV‐related DLBCL may have more aggressive clinical features at presentation in comparison to HCV‐negative patients 39, 40. Other studies have also reported rare lymphoma sites with HCV infection, most notably primary splenic or hepatic41 and ocular adnexal B‐NHL 42. A recent study of 12 HCV‐positive patients identified a new subcutaneous “lipoma‐like” primary extranodal MZL, characterized by subcutaneous nodules containing a lymphoid infiltrate.…”
Section: Manifestations and Subtypes Of B‐nhl Associated With Hcvmentioning
confidence: 99%
“…Patients with HCV‐related DLBCL may have more aggressive clinical features at presentation in comparison to HCV‐negative patients 39, 40. Other studies have also reported rare lymphoma sites with HCV infection, most notably primary splenic or hepatic41 and ocular adnexal B‐NHL 42. A recent study of 12 HCV‐positive patients identified a new subcutaneous “lipoma‐like” primary extranodal MZL, characterized by subcutaneous nodules containing a lymphoid infiltrate.…”
Section: Manifestations and Subtypes Of B‐nhl Associated With Hcvmentioning
confidence: 99%
“…Incisional biopsy should be avoided, even though in cases with uncertain preoperative diagnosis is the key to rule out other malignancies such as orbital lymphoma involving lacrimal fossa which require different treatment modalities and outcome. 9,10 In the present patient, the tumor was completely removed and no recurrence occurred within 3 years of follow-up.…”
Section: Commentmentioning
confidence: 51%
“…These radiological findings suggested a benign tumor of the lacrimal gland. No further distinguishing clinical or blood test features were found (including general diseases frequently associated with orbital lymphoma, such as hepatitis C infection [7]). The patient underwent lateral orbitotomy to remove the lacrimal gland including the whole mass.…”
Section: Methodsmentioning
confidence: 99%